Analisis Pola Pemanfaatan Jaminan Pembiayaan Kesehatan Era Jaminan Kesehatan Nasional Pada Peserta Non PBI Mandiri Di Wilayah Perdesaan Kabupaten Banyumas - Arih Diyaning Intiasari; Julita Hendrartini; Laksono Trisnantoro (Center for Health Policy and Management, 2016)
ABSTRACTBackground : There is a suspected tendency of adverse selection during the implementation of JKN typically among Non PBI members (voluntary member) impact on the high rate of claims for services, especially in the outpatient claims level in hospital. It is necessary to study the patterns of utilization of health financing among Non PBI participants to describe determinants that influence it. Policy recommendations for the improvement of public health financing for non-poor informal sector are expected to support the efforts toward the expansion of the universal health coverageMethod: This study design was cross-sectional in the period from June to December 2015. Data collection is using qualitative approach with in-depth interview guide. Informants are some 24 people comprising 12 Non PBI informant participants, 3 the registrar at the health center, 2 nurses in health centers, 3 the registrar at the private hospital and 4 people registrar in General HospitalResult: There are four patterns of usage by the participants of the Non PBI (Mandiri). The utilization pattern consists of: Utilization of health services appropriate tiered referral system, utilization of health insurance by their own preference of referral system, utilization of health insurance only for health care outpatient and inpatient hospital and utilization of health insurance only for inpatient health services in hospital Conclusion : There is a tendency for adverse selection and moral hazard on utilization of health financing by Non PBI members. Some referral practices are not in accordance with the procedure of tiered referral system due to several identified reasons either from the demand side and the supply side. Keyword : social health insurance, Adverse Selection ABSTRAKLatar Belakang: Adanya kecenderungan terhadap fenomena adverse selection pada skema Non PBI Mandiri berdampak kepada tingginya rasio klaim pelayanan terutama pada klaim rawat jalan tingkat lanjutan di FKTL. Perlu dilakukan kajian terhadap pola pemanfaatan jaminan pembiayaan kesehatan era JKN pada peserta Non PBI Mandiri untuk mengetahui gambaran determinan yang mempengaruhinya. Rekomendasi terhadap perbaikan kebijakan pembiayaan kesehatan masyarakat sektor informal non miskin diharapkan dapat mendukung upaya perluasan kepesertaan menuju kesehatan masyarakat semestaMetode: Penelitian ini menggunakan rancangan potong lintang pada periode Bulan Juni-Desember 2015. Pengambilan data menggunakan pendekatan kualitatif dengan panduan wawancara mendalam. Informan yang terlibat sejumlah 24 orang yang terdiri dari 12 informan peserta Non PBI Mandiri, 3 orang petugas pendaftaran di Puskesmas, 2 orang perawat di Puskesmas, 3 orang petugas pendaftaran di RS Swasta dan 4 orang petugas pendaftaran di RS UmumHasil : Identifikasi pada informan menemukan adanya 4 pola penggunaan jaminan pembiayaan kesehatan oleh peserta Non PBI Mandiri. Pola pemanfaatan tersebut terdiri dari : Pemanfaatan pelayanan kesehatan sesuai sistem rujukan berjenjang, Pemanfaatan jaminan kesehatan dengan sistem rujukan APS, Pemanfaatan jaminan kesehatan hanya untuk pelayanan kesehatan rawat jalan dan rawat inap di FKTL dan pemanfaatan jaminan kesehatan hanya untuk pelayanan kesehatan rawat inap di FKTLKesimpulan: Adanya kecenderungan adverse selection dan moral hazard teridentifikasi pada peserta skema Non PBI Mandiri. Pola pemanfaatan jaminan pembiayaan kesehatan yang tidak sesuai dengan prosedur sistem rujukan berjenjang disebabkan adanya beberapa hal yang dapat teridentifikasi baik dari sisi demand maupun sisi supply. Keyword : BPJS Non PBI Mandiri, Adverse Selection